Freedom of religion and the secular state - Blackford, Russell, 1954- (Malden, MA : Wiley-Blackwell, 2011)
Exploring the relationship between religion and the stateFocusing on the intersection of religion, law, and politics in contemporary liberal democracies, Blackford considers the concept of the secular state, revising and updating enlightenment views for the present day. Freedom of Religion and the Secular State offers a comprehensive analysis, with a global focus, of the subject of religious freedom from a legal as well as historical and philosophical viewpoint. It makes an original contribution to current debates about freedom of religion, and addresses a whole range of hot-button issues that.
Motivation and overview -- A short history of religious intolerance -- Hobbes, Locke, and their legacy: models of the modern state -- Religious impositions and endorsements -- Religion-based morality and the secular state -- Persecution, accommodation, and conscientious objection -- Private power, religious communities, and the state -- Religious freedom and the interests of children -- Religious freedom and freedom of speech -- Back to Locke.
Includes bibliographical references and index.
Keywords: Freedom of religion; Religion and state; Religion; RELIGION -- Religion, Politics & State; Freedom of religion; Religion and state; Electronic books; Electronic books